Insulin Prevents Cardiomyocytes From Oxidative Stress–Induced Apoptosis Through Activation of PI3 Kinase/ Akt - Ryuichi Aikawa; Masao Nawano; Yaping Gu; Hideki Katagiri; Tomoichiro Asano; Weidong Zhu; Ryozo Nagai; Issei Komuro (2000)
Background —Loss of cardiomyocytes by apoptosis is proposed to cause heart failure. Reactive oxygen species induce apoptosis in many types of cells including cardiomyocytes. Because insulin has been reported to have protective effects, we examined whether insulin prevents cardiomyocytes from oxidative stress–induced apoptotic death. Methods and Results —Cultured cardiomyocytes of neonatal rats were stimulated by hydrogen peroxide (H 2 O 2 ). Apoptosis was evaluated by means of the TUNEL method and DNA laddering. Incubation with 100 μmol/L H 2 O 2 for 24 hours increased the number of TUNEL-positive cardiac myocytes (control, ≈4% versus H 2 O 2 , ≈23%). Pretreatment with 10 − 6 mol/L insulin significantly decreased the number of H 2 O 2 -induced TUNEL-positive cardiac myocytes (≈12%) and DNA fragmentation induced by H 2 O 2 . Pretreatment with a specific phosphatidylinositol 3 kinase (PI3K) inhibitor, wortmannin, and overexpression of dominant negative mutant of PI3K abolished the cytoprotective effect of insulin. Insulin strongly activated both PI3K and the putative downstream effector Akt . Moreover, a proapoptotic protein, Bad , was significantly phosphorylated and inactivated by insulin through PI3K. Conclusions —These results suggest that insulin protects cardiomyocytes from oxidative stress–induced apoptosis through the PI3K pathway.